Sistema de gerenciamento de resíduos sólidos de serviços de saúde: diagnóstico e diretrizes para implantação no Hospital de Caridade Frei Clemente - Batista, Aline Ortiz (2013)
The Waste Management Plan for Health Services is a legal requirement that must be met to ensure protection of the environment, protecting workers from the area and the population as a whole. The Charity Hospital Frei Clemente (HCFC) aims to reduce as much as possible risks from the management of different types of waste generated in their wards, especially those by his infectious character, physical and/or chemical, represent high degree of dangerousness. This paper proposed the development of a diagnosis, which reported the current situation and the changes that could be made to ensure improvements. To obtain information regarding HCFC s waste, instruments were used to collect data in the form of questionnaires, worksheets and forms applied in each of the sectors studied, and analysis of documents and interviews addressed. The procedures adopted in each of the stages of waste management of the Hospital were analyzed. According to the results, the total waste generated at the study site was estimated at 1731 kg / month. Participation in percentage of each class of waste was given as follows: Group A waste (infected) 22.18%; residues Group B (Chemical) 7.97%; residues Group D (common) 68 8% and waste group E (sharps) 1.04%. The results from this diagnostic consist of first and major step in the preparation of a Waste Management Plan for Health that might be deployed by the Hospital in question